Montelukast and fluticasone compared with salmeterol and fluticasone in protecting against asthma exacerbation in adults: one year, double blind, randomised, comparative trial. Issue 7420 (16th October 2003) - Bjermer, Leif; Bisgaard, Hans; Bousquet, Jean; Fabbri, Leonardo M; Greening, Andrew P; Haahtela, Tari; Holgate, Stephen T; Picado, Cesar; Menten, Joris; Balachandra Dass, S; Leff, Jonathan A; Polos, Peter G
Abstract: Objectives To assess the effect of montelukast versus salmeterol added to inhaled fluticasone propionate on asthma exacerbation in patients whose symptoms are inadequately controlled with fluticasone alone. Design and setting A 52 week, two period, double blind, multicentre trial during which patients whose symptoms remained uncontrolled by inhaled corticosteroids were randomised to add montelukast or salmeterol. Participants Patients (15-72 years; n = 1490) had a clinical history of chronic asthma for ≥ 1 year, a baseline forced expiratory volume in one second (FEV 1) value 50-90% predicted, and a β agonist improvement of ≥ 12% in FEV 1. Main outcome measures The primary end point was the percentage of patients with at least one asthma exacerbation. Results 20.1% of the patients in the group receiving montelukast and fluticasone had an asthma exacerbation compared with 19.1% in the group receiving salmeterol and fluticasone; the difference was 1% (95% confidence interval -3.1% to 5.0%). With a risk ratio (montelukast-fluticasone/salmeterol-fluticasone) of 1.05 (0.86 to 1.29), treatment with montelukast and fluticasone was shown to be non-inferior to treatment with salmeterol and fluticasone. Salmeterol and fluticasone significantly increased FEV 1 before a β agonist was used and morning peak expiratory flow compared with montelukast and fluticasone (P ≤ 0.001), whereas FEV 1 after a β agonist was used and improvements in asthma specific quality of life and nocturnal awakenings were similar between the groups. Montelukast and fluticasone significantly (P = 0.011) reduced peripheral blood eosinophil counts compared with salmeterol and fluticasone. Both treatments were generally well tolerated. Conclusion The addition of montelukast in patients whose symptoms remain uncontrolled by inhaled fluticasone could provide equivalent clinical control to salmeterol.